Corrosion Behavior of Copper in Biodiesel-diesel-bioethanol (BDE) - Thangavelu, S.K.; Piraiarasi, C.; Abu Saleh, Ahmed; Ani, F.N. (Trans Tech Publications, 2015)
The present study aims to investigate the impact of biodiesel-diesel-bioethanol (BDE) fuel blend on the corrosion behavior of copper. Static immersion tests in B45D35E20 (45% biodiesel, 35% diesel and 20% bioethanol) were carried out at room temperature (25°C) and 50° for 408 hours. Mechanical, physical and chemical properties of copper were investigated before and after immersion tests. Investigations were carried out on the change in morphological properties using optical microscope; change in chemical structure using FTIR; change in mass and volume by weight loss measurement; and hardness changes using universal hardness tester. The changes of fuel properties of the blend such as total acid number (TAN) and color changes were also investigated. The results showed that the corrosion rate of copper in B45D35E20 at high temperature (50°C) is comparatively lower than the previous studies reported for pure biodiesel (B100).